KONTRIBUSI KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA TANGAN TERHADAP HASIL SERVIS ATAS BOLA VOLI TIM SMK MUHAMMADIYAH 1 PEKANBARU - Ahmad Afandi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this study is that the top service skills are still notgood, this is seen when the athlete performs top service, service that sometimes does notenter, deviates and concerns on the net. Where at the time of service for the swing of thearm is less extensive and less strong so that it affects the speed of the ball thatsometimes involves on the net and can also deviate out. This study aims to determinehow much the contribution of arm and shoulder muscle strength and hand eyecoordination on the results of service on volleyball Team of Muhammadiyah 1Vocational School Pekanbaru. This type of research is Correlation to see the level ofrelationship of different variables. The sampling technique is the total population (totalsampling) of Volleyball soccer athletes at the Muhammadiyah Vocational High School1 Pekanbaru, 12 samples of female athletes from Muhammadiayh Vocational School 1Pekanbaru numbered 12 people. This research was conducted at the University ofRiau's Education Education Campus Volleyball Lapanga. The instrument used in thisstudy was Exspanding Dynamometer, tennis ball catch test and top service test. Theresults of the data in this study are top service. Analysis was carried out using multiplecorrelations. Based on data analysis and discussion, it was proven by Rhitung 0.293>Rtable 0.242 with a contribution of 8.58%. Means Rhitung> Rtabel. At the level of ɑ =0.05. Then it can be concluded that there is a contribution of arm and shoulder musclestrength and hand eye coordination on the results of volleyball service at the 1amPekan Baru Military Vocational Team.Key Words: Arm and Shoulder Muscle Strength, Hand Eye Coordination,Upper Service.